2016
DOI: 10.1515/jccm-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ventilation Parameters on Intraabdominal Pressure

Abstract: Introduction: Intraabdominal pressure monitoring is not routinely performed because the procedure assumes some invasiveness and, like other invasive procedures, it needs to have a clear indication to be performed. The causes of IAH are various. Mechanically ventilated patients have numerous parameters set in order to be optimally ventilated and it is important to identify the ones with the biggest interference in abdominal pressure. Although it was stated that mechanical ventilation is a potential factor of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…High intraabdominal pressure can interfere with the normal function of cardiovascular system, pulmonary system and renal system [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…High intraabdominal pressure can interfere with the normal function of cardiovascular system, pulmonary system and renal system [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other reported predisposing factors, such as retching, vomiting, and mechanical ventilation, are associated with increased intra-abdominal pressure. Mechanical ventilation has been identified as an independent risk factor for the development of intra-abdominal hypertension, particularly in critically ill patients and when using parameters of positive end-expiratory pressure and high tidal volumes [ 22 , 23 ]. Stoma prolapse and parastomal hernia are mechanical abdominal wall factors that can result in colostomy wall necrosis and eventual evisceration.…”
Section: Discussionmentioning
confidence: 99%
“…Bunnell and Cheatham investigated patients in a trauma ICU at high risk of developing intra‐abdominal hypertension and abdominal compartment syndrome and found a very poor correlation between IAP and airway pressure . In a study of mechanically ventilated ICU patients, Puiac et al did not find IAP to correlate with pulmonary compliance. In a study of patients with acute respiratory distress syndrome, Krebs et al compared patients with intra‐abdominal hypertension to those with normal IAP and found that there was no difference in gas exchange and respiratory mechanics (lung elastance, chest wall elastance, airway and transpulmonary pressures) between the two groups.…”
Section: Discussionmentioning
confidence: 99%